1996
DOI: 10.1080/00288233.1996.9513162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre‐lamb shearing on feed intake and associated productivity of May‐ and August‐lambing ewes

Abstract: The effects of pre-lamb shearing on feed intake and wool/lamb production of May (autumn)-and August (spring)-lambing ewes were examined. Mixed age Border Leicester x Romney ewes mated to lamb in May or August (60 ewes/ lambing policy) were divided at random into two groups (balanced for pregnancy status and liveweight). One group was shorn on Day 118 of pregnancy (P118) and the second group left unshorn. Measurement of pasture intake was carried out over three periods before lambing (P113-117, P119-130, and P1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Across studies the effects of mid-pregnancy shearing on lamb liveweight at weaning have not been consistent. Mid-pregnancy shearing has been reported to have no effect on weaning weight (Dabiri et al, 1994(Dabiri et al, , 1995a(Dabiri et al, , 1996Husain et al, 1997;Morris and McCutcheon, 1997;Morris et al, 2000;Kenyon et al, 2002b;Revell et al, 2002) or a small increase in the weaning weight of singletons (Smeaton et al, 2000), or twins (Morris et al, 1999) or both singletons and twins (Cloete et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…Across studies the effects of mid-pregnancy shearing on lamb liveweight at weaning have not been consistent. Mid-pregnancy shearing has been reported to have no effect on weaning weight (Dabiri et al, 1994(Dabiri et al, , 1995a(Dabiri et al, , 1996Husain et al, 1997;Morris and McCutcheon, 1997;Morris et al, 2000;Kenyon et al, 2002b;Revell et al, 2002) or a small increase in the weaning weight of singletons (Smeaton et al, 2000), or twins (Morris et al, 1999) or both singletons and twins (Cloete et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…40 However, there were no effects of shearing treatment on organic matter intakes of late pregnant ewes in the present study. This does not agree with studies of non-pregnant and lactating ewes (Wodzicka-Tomaszewska 1964;Webster & Lynch 1966;Elvidge & Coop 1974), in which increased feed intake occurred one week following shearing, but is consistent with many experiments involving late pregnant ewes whether housed in pens (Rutter et al 1972;Symonds et al 1986) or at pasture (Parker et al 1991;Dabiri et al 1995aDabiri et al , 1996. The fact that shearing treatment increases feed intake in non-pregnant and lactating ewes, but not in late pregnant ewes, suggests that this difference is accounted for by the different physiological states of the ewes.…”
mentioning
confidence: 44%
“…This is difficult to achieve in practice because during the winter, when pre-lamb shearing is normally carried out, pasture growth and availability is limited. Furthermore, in many studies of pre-lamb shearing at pasture, responses in feed intake were not evident until some weeks after shearing (Parker et al 1991;Dabiri et al 1995aDabiri et al , 1996. This raises the question of whether high feed allowances immediately after shearing are in fact important.…”
Section: Introductionmentioning
confidence: 99%
“…Dabiri et al (1994) reported an improved fleece weight in pre-lambing shorn ewes in one out of two years. Dabiri et al (1996) also found an increased clean wool production rate in ewes shorn prior to lambing in May, but this effect was absent in ewes shorn prior to lambing in August. Ewes shorn prior to lambing also had higher staple strength and fewer fleeces with mid-staple breaks.…”
Section: Discussionmentioning
confidence: 86%
“…Pre-lambing shorn ewes would be shorn nearer to the period of peak stress associated with reproduction, with fewer mid-staple breaks. An increase in food consumption after shearing prior to lambing could also benefit wool soundness, although this increase was confined to late pregnancy in the study of Dabiri et al (1996).…”
Section: Discussionmentioning
confidence: 99%